(untitled) (REMUNOM, 2026)
The teaching of human anatomy is fundamental in medical training and its contents can be considered one of the most important grounds of the basic cycle of the medical schools. Human Anatomy discipline involves theoretical and practical classes, preferably using cadavers, and features different methodological approaches, complemented by support material based on textbooks and anatomical atlases. In this context, the representation of skin tones diversity in the academic environment - especially in anatomy bibliographical references - is essential for the best training of Brazilian professionals, considering that they will work in a country with a great ethnic and racial variety. Thus, this article aims to survey the main books used in anatomy teaching in Brazilian medical courses that present images of black-skinned individuals. Methodology: A survey was conducted on Political Pedagogical Projects of medical courses offered in Brazil, through public consultations on official university websites. The aim was to identify the basic bibliography recommended in Human Anatomy teaching plans. Results: The results showed that there are few images representing black-skinned individuals in the bibliography collected, showing that the teaching of Anatomy has a predominantly eurocentric history, with representations of white-skinned (Caucasian) individuals. Conclusion: The survey showed that the basic bibliographies used in anatomical studies present few images of black-skinned individuals, revealing a low racial representation in the teaching of Anatomy in Medical courses in Brazil, with a predominance of illustrations of white-skinned (Caucasian) individuals.